BCG and BCGΔBCG1419c transiently protect hypersusceptible I/St mice and induce different influx of macrophages and neutrophils during pulmonary tuberculosis. Issue 1 (17th January 2022) - Korotetskaya, Maria; Baikuzina, Polina; Segura-Cerda, Cristian Alfredo; Aceves-Sánchez, Michel de Jesús; Apt, Alexander; Flores-Valdez, Mario Alberto
Abstract : Background. Host genetic factors influence both susceptibility to Mycobacterium tuberculosis infection and immune responses generated by vaccination. Genetically susceptible mice help to study mechanisms of immune protection which may differ from those operating in more resistant models. Methods. In this work, we compared the efficacy of protection conferred by subcutaneous vaccination of hypersusceptible I/St mice with BCG and the first-generation, hygromycin resistant version of the vaccine candidate BCGΔBCG1419c, against tuberculosis (TB), measured as survival, weight loss and replication in lungs. We further characterized the relative presence of immune cells in lungs. Results. We found that in I/St mice, vaccination with BCG or BCGΔBCG1419c provided similar level of protection against TB-driven weight loss and M. tuberculosis replication in lungs, while prolonging median survival time compared with unvaccinated controls. Despite affording similar protection to parental BCG, BCGΔBCG1419c led to a reduced presence of macrophages in lungs during early TB and to an increased neutrophil recruitment to the lungs during chronic TB. Conclusions. BCGΔBCG1419c protects I/St mice in a different manner than wild-type BCG against pulmonary TB by promoting different influx of macrophages and neutrophils at distinct times post-infection. These findings prompt us to suggest that preclinical evaluation of novel TB vaccine candidates should include evaluation of efficacy not only in commonly used resistant inbred mice, but also in susceptible hosts, to further determine their potential application to populations varying in their genetic. This would likely impact their intended use depending on host resistance or susceptibility to TB.